Exploring the Conceptualization of Teacher Leadership in Namibia - Kamati, Ferdinand Nghifikepunye; Amuthenu, Hileni Silohenda (Indonesian Journal of Education and Social Sciences, 2025)
The purpose of this study was to explore the conceptualization of teacher leadership in Namibia. A case study design was used within the qualitative approach. A sample of 45 participants was selected purposively from three (3) secondary schools. An interview guide, observation schedule, and document analysis were used to collect data from the participants. Data were analyzed using a thematic approach. The literature and the theoretical framework were used to compare and contrast the study findings. The literature and the theoretical framework were used to compare and contrast the study findings. The findings revealed that teacher leadership can be understood in terms of involvement and participation, empowerment, motivation and influence, collaboration, and leading and influence. The study recommends that the Ministry of Education, Arts, and Culture should develop and promote leadership development programs for teachers to understand and practice leadership and review contemporary policies to allow for democratic leadership practices.